Fruit set and yield of pear cultivars as affected by reduced bee pollination period - Benedek, P.; Varga, J. (International Journal of Horticultural Science, 2009)
Results of our experiments prove that pear is more or less sensitive to the reduced bee pollination period. However, the reaction (or the sensitivity) of cultivars may be different to the reduced bee pollination. Most cultivars produce much less yield under reduced bee pollination or no yield with the exclusion of bees but in the case of some cultivars total exclusion of bees does not prevent the yield formation and what is more sometimes reduced bee pollination can be resulted in somewhat higher yield than open pollination. Typical reaction, however, is a significant yield reduction with reduced bee pollination. Pear seems to be somewhat less sensitive to the partial reduction of bee pollination period than apple or quince. The first half of the flowering period seems to be more important in yield formation because usually higher yield was resulted when pear cultivars received open pollination in the first than in the second half of the blooming period. Based on our experimental results no definite relationship between parthenocarpic capacity of cultivars and the yield under reduced bee pollination can be established. So reduced bee pollination does not seem to contribute the parthenocarpic fruit formation in pear.